1972
DOI: 10.1029/ja077i016p02819
|View full text |Cite
|
Sign up to set email alerts
|

Magnetospheric electric fields deduced from drifting whistler paths

Abstract: The amplitude of the E‐W component Ew of the convection electric field in the nightside magnetosphere has been inferred from the observed cross‐L motions of whistler ducts within the plasmasphere. Several ducts distributed over 1–2 RE in L space and over ±15° around the longitude of the Eights, Antarctica, whistler station have been tracked simultaneously. The method appears capable of resolving fluctuations in Ew with period T ∼ 15 min and rms amplitude as low as 0.05 mv/m. For variations with T > 1 hour the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
46
2

Year Published

1981
1981
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(57 citation statements)
references
References 21 publications
9
46
2
Order By: Relevance
“…The most extensive investigations of plasmaspheric electric fields during magnetically disturbed periods are based on incoherent scatter radar results fromn St. Santin [Testud et al, 1975;Blanc et al, 1977;Blanc, 1978] and on the cross-L motions of whistler ducts [Park, 1978;Carpenter et al, 1972Carpenter et al, , 1979. Evans (1972) has presented Millstone Hill radar results showing westward F-region ion drifts of almost 200 m/sec in the afternoon sector on 14 May, 1969.…”
Section: Comparison With Observationsmentioning
confidence: 99%
“…The most extensive investigations of plasmaspheric electric fields during magnetically disturbed periods are based on incoherent scatter radar results fromn St. Santin [Testud et al, 1975;Blanc et al, 1977;Blanc, 1978] and on the cross-L motions of whistler ducts [Park, 1978;Carpenter et al, 1972Carpenter et al, , 1979. Evans (1972) has presented Millstone Hill radar results showing westward F-region ion drifts of almost 200 m/sec in the afternoon sector on 14 May, 1969.…”
Section: Comparison With Observationsmentioning
confidence: 99%
“…Therefore, the conductance is an intermediate variable that can be tuned, such that, even if the field-aligned currents output from the MHD code are incorrect, the potential can still more or less match the empirical potential values (e.g., Ridley et al, 2002). One justification for doing this is that the ionospheric potential is of primary importance for the ring current and plasmasphere (e.g., Carpenter et al, 1972;Sazykin et al, 2002;Liemohn et al, 2002Liemohn et al, , 2005. Therefore, with some tuning of the ionospheric conductances, such that the potential pattern is more accurate, ring current injections and plasmaspheric erosion events can be modeled better.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmapause excursions toward the Earth, detected close to 05 MLT, were explained by the rotation under the satellite of the structures formed in earlier local time sectors (around midnight) under the action of the inferred unsteady electric fields during the substorm. Even earlier whistler research (Carpenter et al, 1972) found that during weak to moderate magnetic storms enhanced cross-L inward drifts close to plasmapause occur preferentially in the 2300-0200 MLT sector and may sometimes occur in a wider region extending to local dawn. Above analyzed MAGION 5 data suggest that these inward drifts possibly result in formation of depleted regions-notches-in the plasmasphere.…”
Section: Comparison With Image Results and Discussionmentioning
confidence: 99%